Game Theory And Competitive Strategy Transportasi Online (Grab And Gojek) Conventional And Sharia Economic Perspective - Muhammad Abdullah Amin Hasibuan (Institut Agama Islam Negeri Padngsidimpuan, 2021)
ABSTRACKIn this discussion the problem is about game theory and competitive strategies from online transportation, namely Grab and Gojek to get customers amid the progress of information, transportation and communication, so that there will be an understanding of the second strategy of Transfortasi mode in the development activities in Indonesia. The methodology in this discussion is descriptive, which is one type of research whose purpose is to present a complete picture of social settings intended for exploration and clarification of a phenomenon or social reality studied, namely grab strategy and Gojek. After the review, it was found that basically the two Transfortasi online modes compete with each other but still prioritize excellent service in the form of ease of ordering, convenience in vehicles, applying cash and non-cash payments, and the most important is vehicle security. In terms of Islamic economic law the activities carried out by the two modes of Transfortasi are not prohibited because they do not violate the rules in the text and alhadist as long as the people associated with them comply with the rules set by the two service providers.